2009
DOI: 10.1093/pcp/pcp178
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Duplicated Nod Factor Receptor 5 (NFR5) Genes in Recessive Loss-of-Function Non-Nodulation Mutants of Allotetraploid Soybean (Glycine max L. Merr.)

Abstract: Chemically induced non-nodulating nod139 and nn5 mutants of soybean (Glycine max) show no visible symptoms in response to rhizobial inoculation. Both exhibit recessive Mendelian inheritance suggesting loss of function. By allele determination and genetic complementation in nod139 and nn5, two highly related lipo-oligochitin LysM-type receptor kinase genes in Glycine max were cloned; they are presumed to be the critical nodulation-inducing (Nod) factor receptor similar to those of Lotus japonicus, pea and Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
75
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(80 citation statements)
references
References 38 publications
0
75
0
5
Order By: Relevance
“…In root cells of the legume hosts, perception is mediated by Nod factor receptors (NFRs) containing ectodomains with three lysin motif (LysM) modules and cytoplasmic serine/threonine kinase domains (4)(5)(6)(7)(8)(9). Mutant studies in the model legumes Lotus japonicus (Lotus) and Medicago truncatula (Medicago) as well as the crop legumes soybean (10,11) and pea (5,6) have shown that NFRs are required for nodulation. Mutant analysis in Lotus identified two NFRs, NFR1 and NFR5, and phenotypic analysis showed that both nfr1 and nfr5 mutants are equally impaired in nodule initiation (4,5).…”
mentioning
confidence: 99%
“…In root cells of the legume hosts, perception is mediated by Nod factor receptors (NFRs) containing ectodomains with three lysin motif (LysM) modules and cytoplasmic serine/threonine kinase domains (4)(5)(6)(7)(8)(9). Mutant studies in the model legumes Lotus japonicus (Lotus) and Medicago truncatula (Medicago) as well as the crop legumes soybean (10,11) and pea (5,6) have shown that NFRs are required for nodulation. Mutant analysis in Lotus identified two NFRs, NFR1 and NFR5, and phenotypic analysis showed that both nfr1 and nfr5 mutants are equally impaired in nodule initiation (4,5).…”
mentioning
confidence: 99%
“…In contrast, the dominant alleles Rj2, Rj3, Rj4, and Rfg1 have unique features that restrict nodulation with specific strains. The dominant nature of these genes is in contrast to the loss-offunction recessive alleles (rj1) in NFRs (18,22,23). Rj2/Rfg1 restricts nodulation with B. japonicum USDA122 and S. fredii USDA257 (24,25).…”
mentioning
confidence: 99%
“…The formation of symbiotic root nodules in soybean plants is controlled by several loci, referred to as the rj or Rj loci (17). The recessive alleles rj1 and rj5 were identified to be putative NF receptors and are referred to as nfr1 and nfr5, respectively (17)(18)(19), and rj7 was identified to be nts1, which is involved in the systemic regulation of nodulation (20,21). In contrast, the dominant alleles Rj2, Rj3, Rj4, and Rfg1 have unique features that restrict nodulation with specific strains.…”
mentioning
confidence: 99%
“…4 As shown by the nod49 and rj1 mutants, GmNFR1β alone in combination with GmNFR5α/β cannot efficiently recognize Nod factor in epidermal and root hair cells to induce root hair deformation, curling and infection thread formation. In contrast GmNFR1α was able to facilitate these steps as shown by functional nodulation in the GmNFR1β Q513* mutant not know whether the GmNFR1β mutation in PI437.654 is causally connected to its nematode resistance phenotype.…”
Section: Isolation Of Gmnfr1α and Gmnfr1β Genesmentioning
confidence: 97%
“…It requires the reception of a Rhizobiumderived 'Nodulation Factor' (NF, a lipooligosaccharide) by a presumptive receptor kinase complex (NFR1/LYK3 plus NFR5/ NFP), both part of the LysM receptor kinase family. [1][2][3][4][5] These Nod factor receptors were not thought to be involved in Myc factor perception, but Maillet et al 6 suggest that NFP, not LYK3 is partly involved in the Myc-signal-elicited root branching stimulation response. In Parasponia andersonii, the only non-legume species that acquired rhizobia symbiosis, a single NFP/ NFR5-like receptor fulfil a dual symbiotic function of both rhizobia and arbuscular mycorrhizae.…”
Section: General Concept Of Nod Factor Perception In Legumesmentioning
confidence: 99%